ANALISIS PENAWARAN JAGUNG DI KABUPATEN WONOGIRI - Setyowati Setyowati (Universitas Sebelas Maret, 2006)
This research aim to analysis factors influencing offer of maize in Sub-Province Wonogiri and also to analysis elasticity level offer of maize Sub-Province Wonogiri. Basic method in this research is descriptive method. Research area determined purposive that is Sub-Province Wonogiri. While used data type in this research is seconder data.